Design Study of a Nuclear Power Plant for 100-Kw Electric and 400-Kw Heat Capacity - Treshow, M.; Snider, A. R.; Shaftman, D. H. (Argonne National Laboratory, 1955)
A conceptional design study was made of a lowpower ''package'' reactor plant for the production of 100 kw of electrical power and 400 kw of heat at remote Arctic installations. The power plant steam generator is proposed to be an unmanned, heterogeneous, boilingtype reactor capable of continuous operation for extended periods. The design is based on data derived from experiments with boiling-type reactors conducted by Argorne at the Reactor Testing Station, Arco, Idaho.